The Application of Big Data Technology and Data Security Guarantee in Archive Management - Sun, Bing (Journal of Theory and Practice of Social Science, 2025)
With the rapid development of information technology, the application of big data technology in the field of archive management is becoming increasingly widespread. Big data technology has brought unprecedented opportunities for archive management, which can optimize archive management processes, improve service quality and efficiency. However, while enjoying the convenience brought by big data technology, data security issues have become increasingly prominent. This article explores in depth the specific application of big data technology in archive management, and proposes data security protection strategies for the security risks faced, aiming to provide reference for the efficient and secure development of archive management work.